Alcohol-Related Problems among Sexual Minority Women - Hughes, Tonda (2011)
In this article I describe the historical context for research on sexual minority women’s drinking, including the age-old tendency to link homosexuality and alcoholism; I summarize gaps and limitations that characterized much of the research on sexual minority women’s drinking over the past several decades; and I review recent literature to highlight progress in the field—with a particular focus on my own research related to risk and protective factors for heavy drinking and drinking-related problems among sexual minority women. I conclude with a discussion of barriers to treatment for sexual minority women and recommendations for substance abuse treatment providers.